Heterogeneity of arthropod communities on the canopy of Ouratea hexasperma (Ochnaceae): does canopy size matter? - Santos, Danillo Alves; Moyses, Wedney; Branco, João Luiz Cordeiro Castelo; Rodrigues, Carlene Gomes; Daud, Rodrigo Damasco (Acta Scientiarum. Biological Sciences, 2025)
Arthropods exhibit high diversity, wide ecological range, broad distribution, and are found in various environments and microhabitats. In the Cerrado biome, many arthropods interact with specific plants, which function as their habitat and foraging grounds. The shrub-tree species Ouratea hexasperma is common in the Cerrado and displays considerable variation in individual canopy size. A direct positive relationship linking area and richness is a widely studied topic in Ecology, with such relationship also being observed in island-like environments. Considering each canopy as an island-like community, in this study, we analyzed the relationship between arthropod richness (measured as family richness) and tree canopy size. We collected and identified 17 arthropod families from nine orders on O. hexasperma trees, with Insecta being the most abundant taxon, followed by Arachnida and Myriapoda. However, Arachnida presented the highest number of families (seven). Our results show a positive correlation between canopy size and arthropod richness, indicating that larger canopies support richer arthropod communities. Thus, our findings support the species-area relationships on small geographic scales.